PI index and edge-szeged index of HC5C7[k, p] nanotubes - Iranmanesh, Ali; Pakravesh Y.; Mahmiani A. (Utilitas Mathematica, 2008)
A C5C7 net is a trivalent decoration made by alternating pentagons C5 and heptagons C7 . It can cover either a cylinder or a torus. In this paper we compute the PI index and Edge-Szeged index of HC5C7[k, p] nanotube.